Procedimentos didático-metodológicos utilizados pelos professores da APAE no processo de alfabetização dos alunos portadores de deficiência mental moderada - Lima, Terezinha de Fátima Aguiar de (2002)
The objective of this research was to identify the didactic and methodological proceeding used by the professors of the APAE in the process of alphabetization of pupils PNEE in the mental area in moderate levei. This research was characterized as being a longitudinal study because I investigated standards of changes occurred during the pertaining to school life of pupils PNEE in moderate mental levei of a special school of the APAE. In this direction, I look for to the long one of the chapters, to direct my quarrels in the attempt to fínd reply to the following questioning: How it is the didactic and methodological guiding used by the professors of the APAE for the developing of the process of reading and writing of the mental classifíed person as defícient moderate? Time-out for in such a way, the population of this study be constitute by the mental defícient consider pupil moderate in accordance with the evaluation prescribe in its individual fiche, and that fínd regular register between the year 1996 the 2000 in the APAE situated city in the region the northwest of the State of the Paraná. Amongst the population of 252 pupils PNEE in moderate mental levei of the special school APAE. chosen for the research, I intentionally selected only those that took care of to the established criteria its respective folders to compose the sampling of my study. Thus, I studied five pupils in a total of 25 folders, being that the studied folders belonged to the classrooms and distinct professors. In structural terms, this dissertation thus is organized: in the fírst chapter I present the beddings of the special education, standing out the historical process of creation and framework of the APAE in Brazil and the State of the Paraná; in as the chapter I argue the different conceptions conceming that it comes to be mental defíciency e, more specifically, what he has been understood as moderate mental defíciency; in the third chapter I present considerations conceming the process of acquisition of the reading and the writing in general mode e, later, of more specifíc form, on the carriers of mental defíciency in moderate mental levei. In the room chapter I analyze and I argue the methodological guiding used by the professors of the APAE during the process of alphabetization of the carrying pupils of mental defíciency in moderate levei. It concludes that the used by the professors of APAE in the process of alphabetization of pupils PNEE in moderate mental levei is based in an education proposal traditional. Thus, the objectives, the strategies of education and the type of evaluation do not consist in a proposal innovative capable to propitiate to the pupils the signifícant development of the reading and the writing. Results joined point, therefore, for necessity of professors to direct guiding methodological differentiated, where the carrying child of mental defíciency pass to be the Citizen in the fetching of its knowledge making possible, to the child to go beyond the concrete knowledge, what it implies stimulates it to codify it its experiences, or either, to represent operating with symbols.